Recent Developments Studies on Wood Protection Research in Academia: A Review - Khademibami, Laya; Bobadilha, Gabrielly S. (Frontiers in Forests and Global Change, 2022)
The wood preservation industry has taken large leaps to develop and produce chemicals that protect wood from microorganisms and weathering degradation with no or low environmental impact. These improvements occurred after concerns of federal and public agencies about the release of toxic components into atmosphere, soil, and water. These days, reduction in use of non-renewable resources is a crucial concern. Wood and wood-based products are generally low in CO2 emissions and can be gained from sustainable forest resources. Therefore, they can play a significant role as renewable resources. In comparison to other building materials, wood has numerous advantages, such as suitable thermal insulation, high strength to weight ratio, easy machinability, and attractive esthetics. Wood as a valuable building and industrial material requires to be protected due to its biodegradable properties especially when it is submitted to harsh conditions. Wood durability can be improved through wood protection which include wood preservatives and modification systems. Wood protection should be safe to use, efficient, cost-effective, permanent, and should not corrode metal or degrade wood components. Numerous reviews of wood protection can be found in the scientific literatures, but until now a review of a combination of wood preservation and wood modification has not been studied. It should be considered that the latest research projects in wood protection in academia not always reflect the most current developments in the industry due to exclusive rights. The findings reported in academia contribute to the safe use of preservatives, advancement of wood modification techniques, as well as recycle and disposal of treated material. Therefore, in this study, the most current research and advancements promoted in the wood protection in academia are discussed which including an overall summary of the recent developments on wood preservatives, different types of preservatives, natural preservative compounds, and modification technologies in academia.